OpenBravo ERP in Enterprise Company - Mario Joseph Christianto (Jurnal Sosial Teknologi, 2022)
This paper aims to find out the extent of the use of OpenBravo software in an enterprise's ERP. Then compare OpenBravo with other Open Source ERP applications like Odoo.  Enterprise Resource Planning (ERP) plays an important role in organizational management. especially in the field of information systems, to produce precise and accurate data. OpenBravo is web-based software and open-source web-based ERP solution for small and medium-sized enterprises and is released under the OpenBravo PublicLicense, under the Mozilla Public License. Openbravo provides a web-based interface, where users can view production, inventory, customer information, order tracking, and workflow information. The modules contained in Openbravo software include general settings, master data management, warehouse management, procurement management, project and service management, production management, sales management, and financial management.  In this case, the ERP used is OpenBravo. Comparison with other types of ERP will be carried out and will be discussed in more detail related to the advantages and disadvantages of each ERP discussed. After the comparison and the advantages and disadvantages are discussed, then finally conclusions are made from all the discussions carried out. In this case, the writing methodology used to complete this paper comes from a literature study which contains several things such as the concept of OpenBravo, how OpenBravo works, and the advantages and disadvantages of OpenBravo when compared to other ERPs.